2012
DOI: 10.4012/dmj.2011-256
|View full text |Cite
|
Sign up to set email alerts
|

Filler size of resin-composites, percentage of voids and fracture toughness: is there a correlation?

Abstract: The objective of this study was to investigate the correlation between fi ller size, fracture toughness and voids. Seven model resin composites and one commercial have been used in the study. A single edge notch mould was used to prepare samples (n=8). A selected area of 1mm below and above the notch was scanned with micro CT and then the percentage of voids calculated. A universal testing machine was used to measure fracture toughness. Percentage of voids and fracture toughness data were analysed using ANOVA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 22 publications
1
23
0
2
Order By: Relevance
“…1. That corroborates to the findings in previous studies [11][12][13]. The presence of pores in glass-ionomers microstructure can be attributed to the following factors: air incorporation during powder and liquid hand-mixture that decreases the polymer conversion degree due to inhibition of the setting reaction by the oxygen in the bubbles; placement technique of the material into the tooth cavity where the air bubbles are incorporated or entrapped into the material; and changes in powder/ liquid proportion before mixture [13,14].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…1. That corroborates to the findings in previous studies [11][12][13]. The presence of pores in glass-ionomers microstructure can be attributed to the following factors: air incorporation during powder and liquid hand-mixture that decreases the polymer conversion degree due to inhibition of the setting reaction by the oxygen in the bubbles; placement technique of the material into the tooth cavity where the air bubbles are incorporated or entrapped into the material; and changes in powder/ liquid proportion before mixture [13,14].…”
Section: Discussionsupporting
confidence: 80%
“…A slower mixing can avoid air incorporation by breaking some bubbles [13,15]. Considering dental resin composites, the formation of pores can occur during the manufacturing process [12].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the filler content of a sealant increases its viscosity. 32 When SEP is used to prepare the tooth surface, even though most of the primer is removed, a thin layer remains after air drying. When a bracket having a 70%-filled composite is applied to this primer layer, the resin might be viscous enough to maintain its integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in an unrelated study using composites made from these same fillers, it was shown that wear was also reduced with spherical fillers [4]. More recently, these same fillers were used to investigate the effect of filler size on void formation and fracture toughness of experimental composites [12]. The study showed that void formation was enhanced in composites with larger fillers (but the same filler volume), from a low of 0.27 % voids for a composite with a trimodal distribution of irregular and spherical fillers to a high of 3.53 % for a composite with a unimodal distribution of 1500-nm irregular fillers.…”
Section: Surface Finishmentioning
confidence: 99%